Dielectric Performance of Vegetable Oil Based Silicone Dioxide and Copper Oxide Under High Temperature Ageing (ELEKTRIKA- Journal of Electrical Engineering, 2025)
This experimental study aims to ascertain the characterization of Vegetable Oil (VO) based nanofluid with SiO2 and CuO nanoparticles, the AC breakdown voltages and the partial discharge (PD) activities of mineral oil (MO) and VO based SiO2 and CuO nanofluids under high-temperature ageing. Various concentrations range of SiO2 and CuO dispersed in oil samples varied from base to 0.05%. In total, one sample of refined, bleached and deodorized palm oil (PO) and one sample of MO were measured for PD. The AC breakdown voltages measurement for all samples were carried out. Maximum PD amplitude measurements were conducted with a gap distance of 25 mm and by using needle-sphere electrode configuration for this study. The formation of SiO2 and CuO in Refined Bleached and Deodorized Palm Oil (RBDPO) is proven through the characterization using the FTIR. Then, the SiO2 and CuO nanoparticles are confirmed by using the X-ray Diffraction (XRD) and by comparing the experimental data with the Material Project software. SiO2 and CuO could improve the performance of AC breakdown voltage of MO and RBDPO for 14 and 28 days of ageing. The most significant improvements in PD activities are observed at 28 days of ageing where the maximum PD amplitude shows the highest decrement for MO based SiO2 and CuO nanofluids with 71.7% and 80.1% respectively. For RBDPO based SiO2 and CuO nanofluids provide the highest decrement at 14 days with 34.2% and 28 days with 49.5% respectively.
Keywords: Partial Discharge; AC breakdown; silicon oxide; copper oxide; nanofluids